2004
DOI: 10.1577/t03-223.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosystem, Dam, and Reservoir Passage Rates of Adult Chinook Salmon and Steelhead in the Columbia and Snake Rivers

Abstract: We assessed upstream migration rates of more than 12,000 radio-tagged adult Chinook salmon Oncorhynchus tshawytscha and steelhead O. mykiss past a series of dams and reservoirs on the Columbia and Snake rivers. Most fish passed each dam in less than 2 d. Migration behavior in reservoirs and through multiple dam-reservoir reaches varied within and between years and between species. Within years, spring-summer Chinook salmon migrated more rapidly as water temperature and date of migration increased; between year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
162
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 107 publications
(175 citation statements)
references
References 49 publications
12
162
1
Order By: Relevance
“…The imperative of reaching spawning grounds at appropriate times may have prompted adult salmon to continue migration even when temperature conditions were suboptimal. This behavior contrasts with that from similar analyses for adult steelhead O. mykiss, where we found stronger relationships between temperature, passage rates, and the proportions of radio-tagged fish that temporarily entered lower river tributaries (Keefer et al 2004a;High et al, in press). Associations between water temperature and salmonid distributions and behaviors have been relatively well-studied because of the species' commercial, recreational, and ecological importance.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The imperative of reaching spawning grounds at appropriate times may have prompted adult salmon to continue migration even when temperature conditions were suboptimal. This behavior contrasts with that from similar analyses for adult steelhead O. mykiss, where we found stronger relationships between temperature, passage rates, and the proportions of radio-tagged fish that temporarily entered lower river tributaries (Keefer et al 2004a;High et al, in press). Associations between water temperature and salmonid distributions and behaviors have been relatively well-studied because of the species' commercial, recreational, and ecological importance.…”
Section: Discussioncontrasting
confidence: 99%
“…And although some stocks, particularly steelhead, have some flexibility with which to react to prevailing river flow and temperature conditions (Robards and Quinn 2002;Keefer et al 2004a), flexibility in migration timing generally appears to be limited for salmonids. Quinn and Adams (1996) observed that return timing for Columbia River sockeye salmon was less variable over time than for nonindigenous American shad Alosa sapidissima, and suggested that migration timing for sockeye salmon was less plastic than for the introduced species and did not match the rate of environmental change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the proportion sampled each day varied slightly, and we did not sample at night because few adult salmon and steelhead pass dams at night (Robards and Quinn, 2002;Keefer et al, 2004b;Naughton et al, 2005). During the 2-year study transmitters were placed in 3355 Chinook salmon and steelhead in 2001 and 3555 fish in 2002.…”
Section: Fish Trapping and Taggingmentioning
confidence: 99%
“…dams, generating stations) and operations can interrupt a river's natural flow regime, fish habitat, and system connectivity, and thus has the potential to negatively influence the upstream migration of fish, particularly anadromous fish such as salmonids that must travel upriver to natal spawning grounds (Poff et al 1997, Enders et al 2009). Recent studies have demonstrated delays (Thorstad et al 2003, Keefer et al 2004, 2008, Pon et al 2009a or failure of mature adult salmon to reach spawning grounds (e.g. Gowans et al 2003, Thorstad et al 2003 and higher energetic costs for salmonids exposed to variable water flows (Murchie & Smokorowski 2004, Tiffan et al 2010 in regulated rivers.…”
Section: Introductionmentioning
confidence: 99%